Still counting: new records, nomenclatural notes, and three new species of Phaeogenini (Hymenoptera, Ichneumonidae, Ichneumoninae) from the Afrotropical region - Dal Pos, Davide; Claridge, Brandon; Diller, Erich; Van Noort, Simon; Di Giovanni, Filippo (European Journal of Taxonomy, 2023)
A synthesis of the Phaeogenini occurring in the Afrotropical region is provided. Three species are newly described: Centeterichneumon nambi Dal Pos, Diller & Di Giovanni sp. nov. from Uganda, Chauvinia ganota Claridge sp. nov. from Kenya, and Kibalus nonnaritae Dal Pos & Di Giovanni sp. nov. from Uganda. Heterischnus mfongosi Rousse & van Noort, 2013 is newly recorded for Kenya and Tanzania and the male of the species is diagnosed for the first time. Also, the female of Arearia oxymoron Rousse & van Noort, 2013 is diagnosed for the first time from one of the paratype localities. Lusius tenuissimus (Heinrich, 1938) and Chauvinia nyanga Rousse & van Noort, 2013 are recorded for the first time for Uganda and Kenya, respectively. In addition, new localities are given for Chauvinia nitida (Heinrich, 1938), Heterischnus olsoufieffi (Heinrich, 1938) and Hoplophaeogenes curticornis Heinrich, 1938. A new combination, Nesostenodontus mkomazi (Rousse & van Noort, 2013) comb. nov., is proposed to accommodate Heterischnus mkomazi. An updated key to the Afrotropical genera of Phaeogenini and keys to the Afrotropical species of the genera Arearia Seyrig, Centeterichneumon Heinrich, Chauvinia Heinrich, Heterischnus Heinrich, Hoplophaeogenes Heinrich, Kibalus Rousse, van Noort & Diller, and Lusius Tosquinet are provided. Updated online Lucid keys to genera and species are available from http://www.waspweb.org.